2018
DOI: 10.5812/zjrms.10698
|View full text |Cite
|
Sign up to set email alerts
|

The Combined Effect of Resistance Training and Green Tea Supplements on the Lipid Profile and Anthropometric Indices of Overweight and Obese Males

Abstract: Background:The prevalence of obesity has led to an increase in research on obesity and cardiovascular disease and its metabolic risks.Objectives: This research aimed at exploring the combined effect of resistance training and green tea supplements on the lipid profile and anthropometric indices of overweight and obese males in a definite period of time. Methods:In this clinical trial study, 60 males aged 34 ± 8 with a body mass index (BMI) of 29.88 ± 2.08 Kg.m -2 were randomly assigned to four groups of 15, na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Nonetheless, the interaction effect of these two separate factors has been received less attention. Although the combination of RT with GT intake resulted in a significant improvement in body composition and several blood lipids, 26 it has been reported that the addition of GT consumption to an aerobic training protocol was not effective to modify other cardiovascular risk factors such as HR. 27 In contrast, our previous results showed that three weeks consumption of GT have a favorable effect on RPP and MBP responses to an acute session of RT.…”
Section: Introductionmentioning
confidence: 97%
“…Nonetheless, the interaction effect of these two separate factors has been received less attention. Although the combination of RT with GT intake resulted in a significant improvement in body composition and several blood lipids, 26 it has been reported that the addition of GT consumption to an aerobic training protocol was not effective to modify other cardiovascular risk factors such as HR. 27 In contrast, our previous results showed that three weeks consumption of GT have a favorable effect on RPP and MBP responses to an acute session of RT.…”
Section: Introductionmentioning
confidence: 97%